Conceptual World Picture in the Danubian Communities’ Language Consciousness: Array - Soroka, Tetiana (Journal of Danubian Studies and Research, 2020)
The article is focused on integral research of linguacognitive structure of concepts reflected in linguistic consciousness of native speakers of the Danubian communities. The stages and ways of concepts’ studying; the structure of concept and its determinations existing in modern science are analysed, as well as the phenomenon “concept” is separated from contiguous notions and terminological synonyms. The field approach is grounded to the analysis of concepts; the principles of conceptual analysis are foreshortened in a semantic field. Based on the forming meanings the content of concepts is determined. The sense filling of the concepts is exposed in the nuclear planes and on the peripheral areas within the limits of the semantic fields. The typical and nationally-specific semantic constituents of explored concepts of the noted ethnic associations are found out.